The climate change plan meeting the emissions reduction targets 2018-2032 : the third report on proposals and policies : written statement laid before the Scottish Parliament pursuant to section 35 of the Climate Change (Scotland) Act 2009.: the third report on proposals and policies : written statement laid before the Scottish Parliament pursuant to section 35 of the Climate Change (Scotland) Act 2009. (2018) - Unknown
No abstract available